Brazilian Fig Plantations Are Dominated by Widely Distributed Drosophilid Species (Diptera: Drosophilidae) - Roque, F.; Matavelli, C. [UNESP]; Lopes, P. H. S.; Machida, W. S.; Von Zuben, C. J. [UNESP]; Tidon, R. (Oxford Univ Press Inc, 2017)
Although cultivated and degraded lands outnumber natural ecosystems in many regions of the world, there are relatively few studies focusing on their biodiversity. Here, we investigated the drosophilid assemblages recorded in eight Brazilian fig plantations and discussed probable invasive species among the identified fauna. Each plantation was sampled monthly, from September 2010 to August 2011, using five drosophilid retention traps arranged in an 80-m transect. The 125,428 drosophilids captured represent 52 nominal and 10 unidentified species belonging to eight genera: Diathoneura Duda, Drosophila Fallen, Neotanygastrella Duda, Rhinoleucophenga Hendel, Scaptodrosophila Duda, Scaptomyza Hardy, Zaprionus Coquillett, and Zygothrica Wiedemann. Besides this rich diversity, our samples were dominated by widespread generalists representing exotic and neotropical species: Zaprionus indianus Gupta, Drosophila simulans Sturtevant, Scaptodrosophila latifasciaeformis (Duda), Drosophila sturtevanti Duda, Drosophila mercatorum Patterson and Wheeler, Drosophila cardini Sturtevant, and Drosophila buzzatii Patterson and Wheeler. These species should be carefully monitored, especially in the first half of the year, to prevent environmental and economic losses due to their eventual introduction in new areas.
Keywords: agriculture; biodiversity; fly; invasion